Portal da educação ambiental - PAPARIDIS, Otávio Soares (2019)
Education as a basic social right of Brazilians is guaranteed in the Federal Constitution of 1988. In the educational field, considering the current scenario of intense environmental degradation, it is necessary to work on environmental education. But for the effective preservation of the environment, measures that aim at the inclusion and participation of the entire community are indispensable, and in this context, it is not possible to forget about people with disabilities who encounter barriers in the execution of basic daily activities. Education is the gateway to all other rights and makes it possible to act in society. Thus, it is necessary to think about measures capable of truly including these people and guarantee their effective exercise of citizenship. However, including people with disabilities requires some changes in the physical space and/or methods used, especially for people with visual impairment, whose educational barriers are enormous, since most educational content depends on the use of sight. Thus, to guarantee the accessibility of these people there are some mechanisms for overcoming barriers, such as assistive technologies and guidelines established to guarantee web accessibility, as well as the use of open educational resources, considering that currently the internet occupies great space in life people and in the educational process. In this sense, the main objective of this work is to help people with disabilities, especially visual ones, to have access to environmental education, enabling them to be at the center of debates about the subject, and to exercise their right to citizenship. In addition, it has as specific objective the elaboration of a website accessible to these people, with content on environmental education, free of charge and in the form of an open educational resource. Through the use of a content management system, as well as the adoption of functionalities on the website and access to content made available in OER format, it was possible to create the Environmental Education Portal, whose accessibility was validated by AChecker, obtaining a level of compliance AA. The portal can be accessed through the website www.educacaoambiental.online and through it people with visual impairments can learn about forests, water resources, biodiversity, sustainable agriculture and environmental education, since all contents are accessible.